How to convert digital offerings into revenue enhancement : Conceptualizing business model dynamics through explorative case studies - Gebauer, Heiko; Arzt, Alexander; Kohtamäki, Marko; Lamprecht, Claudio; Parida, Vinit; Witell, Lars; Wortmann, Felix (Elsevier, 2020)
Equipment manufacturers are currently utilizing new digital technologies such as the Internet of Things (IoT), Artificial Intelligence, or Big Data, for new digital offerings. However, these offerings seldom enhance revenue, because companies struggle with business model (BM) dynamics. By analyzing 27 companies through an explorative case-study approach, the authors consider how companies can successfully achieve revenue enhancement through digital offerings. The result is a threefold framework for revenue enhancement through digital offerings. First, this framework distinguishes between three phases of BM dynamics: 1) augmenting products through a “hardware plus” logic, 2) developing a portfolio of multiple logics for creating customer value, 3) integrating this portfolio through platform logic. Second, the framework emphasizes that three barriers, which we refer to as confidence, mixing, and collaboration barrier, limit the progress from Phases 1 to 3. Third, the framework reveals that each phase contains certain modifications of BM components. In the first phase, companies adapt their BM components slightly, so as to advance toward a “hardware plus” logic. In the second phase, companies embrace more radical BM innovations in order to convert services into an outcome-based BM and develop a new software subscription BM. In the third phase, companies modify BM components in order to integrate the BMs internally and to open them up for external collaboration partners.
Keywords: Business model components; Business model innovations; Competitive advantages; digitalization; Digital offerings; Revenue enhancement; business models; value creation; Strateginen johtaminen